Answer:
True
Explanation:
We have given that P(A) and P(B) are mutually exclusive
Mutually exclusive means there is no common element in A and B
So [tex]P(A\cap B)=0[/tex]
We know that [tex]P(A\cup B)=P(A)+P(B)-P(A\cap B)[/tex]
As A and B are mutually exclusive and so [tex]P(A\cap B)=0[/tex]
Putting this value in [tex]P(A\cup B)[/tex]
[tex]P(A\cup B)=P(A)+P(B)-0=P(A)+P(B)[/tex]
From the above equation we can see that [tex]P(A\cup B)[/tex] is the sum of [tex]P(A)[/tex] and [tex]P(B)[/tex]
So the given statement is true statement